2011
DOI: 10.3390/molecules16032293
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Determination of Flavonoids in Astragali Radix by High Performance Liquid Chromatography Coupled with DAD and ESI-MS Detection

Abstract: A method for the analysis of flavonoids in Astragali Radix by high-performance liquid chromatography (HPLC) combined with photodiode-array detection (DAD) and an electrospray ionization (ESI) - mass spectrometry (MS) was developed. After the samples were extracted with ethanol, the optimum separation conditions for these analytes were achieved using a gradient elution system and a 2.0 × 150 mm Shimadzu VP-ODS column. Eight flavonoids were identified to exist in Astragali Radix based on their characteristic UV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…The major polysaccharides present in Astragalus are mannose, d -glucose, d -galactose, xylose, and l -arabinose (Kallon et al 2013 ). The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…The major polysaccharides present in Astragalus are mannose, d -glucose, d -galactose, xylose, and l -arabinose (Kallon et al 2013 ). The major flavonoids of Astragalus are 3-O-β- d -glucoside, 2′-hydroxy-3′,4′-dimethoxyisoflavane-7-O-β- d -glycoside, 7,3′-dihydroxy-4′-methoxyisoflavone, 7,3-dimer-capto-4,1-methoxyisoflavone, 3-dimercapto-7,4,1-methoxyisoflavone, and kumatakenin (Lv et al 2011 ; Xiao et al 2004 ). A recent study showed that crude extracts of Astragalus are anti-inflammatory (Kim et al 2013 ), anti-viral (Zhang et al 2018 ), immunostimulatory (Zhang et al 2017 ), promote growth performance (Li et al 2018 ) and affects fecal microbiota of young hens (Qiao et al 2018a ).…”
Section: Introductionmentioning
confidence: 99%
“…Our recent study using a multiple reaction monitoring-based approach revealed over 400 flavonoids in the herb, among which around 130 are calycosin (7,39-dihydroxy-49-methoxyisoflavone) and its glycosides . As the most abundant and characteristic flavonoid compound in Astragali Radix (Lv et al, 2011), calycosin-7-O-b-D-glucoside (C7G) has been documented in the China Pharmacopoeia (Chinese Pharmacopoeia Commission, 2010) as one of the markers for quality control of the herb. Recently, this herb has been acclimated to European countries for phytotherapeutic purposes (Matkowski et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have focused on component determination on each herb included in FGF, such as Radix Astragali (Lv et al ., ; Qi et al ., ; Song et al ., ; Wu et al ., ; Zu et al ., ), Radix Angelicae Sinensis (Qi et al ., , ; Wu et al ., ; Yi et al ., ), Flos Carthami (Chen et al ., ; Fan et al ., ; Sun et al ., ; Wang et al ., ), Radix Gentianae (Li et al ., ; Yang et al ., ) and Caulis Spatholobi (LiYing, ; Qixin Yan, ; Zheng et al ., ), no report exists on methods available for quantitative analysis of the multiple components of FGF.…”
Section: Introductionmentioning
confidence: 99%